2016
DOI: 10.1080/09542299.2016.1198928
|View full text |Cite
|
Sign up to set email alerts
|

Interface interactions between insecticide carbofuran and tea waste biochars produced at different pyrolysis temperatures

Abstract: Biochars showed a potential as adsorbents for organic contaminants, however, have not been tested for carbofuran, which has been detected frequently in water. This study provides evidences for the use of infused tea residue derived biochar for carbofuran removal. Biochars were produced at 300, 500 and 700 °C by slow pyrolysis and were characterized by proximate and ultimate analysis, FT-IR, SEM, BET and pore size distribution. Pyrolysis temperature showed a pronounced effect on biochar properties. The maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…The BET surface area for the UTAC prepared by chemical activation with phosphoric acid was found to be 243 m 2 g -1 , which is in good agreement with the values reported in literature under same conditions [27][28][29]. However, activated carbon produced in our study showed higher BET surface area than tea or lignocellulosic materials already reported in literature [24,25,30,31]. The BET surface area of Fe-UTAC was 165 m 2 g -1 .…”
Section: Characterization 311 Surface Area and Pore Size Distributionsupporting
confidence: 91%
See 1 more Smart Citation
“…The BET surface area for the UTAC prepared by chemical activation with phosphoric acid was found to be 243 m 2 g -1 , which is in good agreement with the values reported in literature under same conditions [27][28][29]. However, activated carbon produced in our study showed higher BET surface area than tea or lignocellulosic materials already reported in literature [24,25,30,31]. The BET surface area of Fe-UTAC was 165 m 2 g -1 .…”
Section: Characterization 311 Surface Area and Pore Size Distributionsupporting
confidence: 91%
“…Although activated carbon prepared from spent tea leaves, industry e-mail: tahiramahmood@uop.edu.pk. tea waste or tea waste biochar has been used for the adsorption of organic contaminants such as dyes, phenols and pesticides from aqueous solutions [23][24][25], however, it has not been tested for heavy metals particularly As(III). To the best of our knowledge, no former work has reported activated carbon from used tea (household) and iron oxide (magnetite) impregnated used tea activated carbon (Fe-UTAC) for the selective removal of As(III) ions.…”
Section: Introductionmentioning
confidence: 99%
“…Carbofuran sorption onto biochar through p-p electron donoracceptor interactions can occur. 28,29 Such p-p electron donoracceptor interactions are well known for the sorption of organic contaminants onto carbonaceous activated carbons and biochars. In the acidic medium, the protonated carbofuran can interact with the electron rich regions of graphene-like surfaces of SB500, giving rise to strong p-p electron donor-acceptor interactions, as shown in Scheme 5, where the protonated carbofuran is the p-electron acceptor.…”
Section: Effect Of Ph On Carbofuran Removal and Sorption Mechanismmentioning
confidence: 99%
“…17 Overexposure to carbofuran results in abdominal cramping, blurred vision, coma, convulsions, headache, nausea, tremors, and weakness. 17 Photolysis, [18][19][20][21] ozonation, 22,23 UV-irradiation, 24 advanced oxidation, 22 nanoltration and osmosis 25 and adsorption [26][27][28][29] are currently used for aqueous carbofuran removal. Activated carbon sorption in water is the most frequently employed method as compared to other methods; 30,31 however, the use of activated carbon is not very cost effective; thus, there is an urgent requirement to nd low-cost, sustainable and effective adsorbents for the removal of carbofuran at varying concentrations from water.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds such as carbaryl, methomyl, carbofuran and methiocarb are among the carbamate insecticides commercially registered. The natural products cocaine, scopolamine and atropine are examples of tropane alkaloids that exhibit insecticidal activity.…”
Section: Resultsmentioning
confidence: 99%